Major and trace element geochemical analyses from “The mean composition of ocean ridge basalts” and “Enriched basalts at segment centers: The Lucky Strike (37°17′N) and Menez Gwen (37°50′N) segments of the Mid-Atlantic Ridge” - Gale, Allison (Interdisciplinary Earth Data Alliance (IEDA), 2013)
Supplementary tables from “The mean composition of ocean ridge basalts” and “Enriched basalts at segment centers: The Lucky Strike and Menez Gwen segments of the Mid-Atlantic Ridge”. Tables include: (1) Major and trace element analyses and isotopic analyses of a global compilation of mid ocean ridge basalts. (2) Major and trace element compositions of glasses and glassy basalts from KP-2,3,5 and PO-1
Gale, A., C. A. Dalton, C. H. Langmuir, Y. Su, and J.-G. E. Schilling (2013), The mean composition of ocean ridge basalts, Geochem. Geophys. Geosyst., doi:10.1029/2012GC004334.

Gale, A., S. Escrig, E. J. Gier, C. H. Langmuir, and S. L. Goldstein (2011), Enriched basalts at segment centers: The Lucky Strike (37°17′N) and Menez Gwen (37°50′N) segments of the Mid‐Atlantic Ridge, Geochem. Geophys. Geosyst., 12, Q06016, doi:10.1029/2010GC003446.
Keywords: Global; Global; Spreading Center; Chemistry:Rock; Geochemistry; FOS: Earth and related environmental sciences; FOS: Earth and related environmental sciences; Marine Geoscience; Solid Earth; basalt; isotopes; major elements; mid-ocean ridge; Ridge related; trace elements; East Pacific Rise; Gakkel Ridge; Lucky Strike; Menez Gwen; Mid-Atlantic Ridge; Reykjanes Ridge